Effectiveness of Java Chili Extract (Piper retrofractum Vahl.) to Leukocyte Reduction on Wistar Rats with Traumatic Ulcers - Rizky Nurhidayah; Risyandi Anwar; Lisa Oktaviana Mayasari (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2019)
Background: Oral traumatic ulcer is an ulcerative lesion of the oral mucosa caused by trauma. The prevalence of traumatic ulcers is quite high between the other oral lesions. Handling traumatic ulcer use corticosteroids that have the effect of increase the growth of Candida sp. in the oral cavity (candidiasis). Objective: To determine the effect of Java chili extract (Piper retrofractum Vahl.) on leukocyte reduction in Wistar rats with traumatic ulcer. Methods: This is experimental laboratory study with pre and post test with a control group design. The research sample using 20 male Wistar rats, weight ±150 grams, 2-3 months old, divided into 4 treatment groups, (K1) group with untreated ulcers, (K2) rats with ulcers treated with iodine, (K3) rats with ulcers treated with java chili extract 50%, (K4) rats with ulcers treated with java chili extract 100%.The research was analyzed by different test with dependent sample t test. Results: The results showed a value of p <0.05 for all comparisons between the two groups showed that there were differences between the two groups compared have a significant difference in the number of leukocytes so it was known that Java chili extract decreased the number of leukocytes in Wistar rats with traumatic ulcers. Conclusion: Java chili extract (Piper retrofractum Vahl.) was effective in decreased the number of leukocytes in Wistar rats with traumatic ulcers.